The Mediation Role of Job Satisfaction in the Relationship Between Compensation and Work Environment on Employee Performance at the YBE Bright Clinic, Semarang - Christika Sandra Pramesti; Irawan Yuswono (Nomico, 2025)
This study aims to analyze the influence of compensation and work environment on employee performance with job satisfaction as a mediating variable at the YBE Bright Clinic in Semarang City. This study is based on Herzberg's Two-Factor Theory, which emphasizes the importance of motivation and hygiene factors in influencing job satisfaction and performance. This study used a quantitative method with 200 respondents who were permanent employees and selected through a census. Data were collected through a survey using a questionnaire and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results showed that compensation and work environment significantly influenced job satisfaction. Work environment and job satisfaction also had a positive effect on employee performance, while compensation did not have a direct effect on performance. Job satisfaction was proven to mediate the effect of compensation on employee performance. The research model was declared feasible with an SRMR value of 0.056, which is below the cut-off limit of 0.08. These findings emphasize the importance of building a conducive work environment and a supportive compensation system to improve employee satisfaction and performance.